Raspberry Pi as a low-cost data acquisition system for human powered vehicles - Ambrož, Miha (Measurement : journal of the International Measurement Confederation, 2017)
[Display omitted] •Use of Raspberry Pi for riding dynamics data acquisition of a bicycle was researched.•Prototype system for sampling analogue and digital inputs was developed and built.•The system was successfully tested in the laboratory and in the field on a bicycle.•The performance is comparable to costlier and less portable data acquisition systems. The presented work was conducted to test the hypothesis that a Raspberry Pi Model B single board computer can be applied as a riding dynamics data acquisition system for use on human powered vehicles. The research of the subject was followed by the development, which led to a working prototype of such a data acquisition system. The procedure included the system component integration, system software setup and data acquisition software development. The prototype system was tested in laboratory conditions, and in the field using a bicycle as the test vehicle. The results prove the initial hypothesis and confirm that the performance of the developed system is comparable to some higher-priced and less portable data acquisition systems. Other possibilities of application of the developed system and intended future improvements are discussed in the final part of the paper.